2016
DOI: 10.1097/tp.0000000000001222
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF-α Agent Infliximab and Splenectomy Are Protective Against Renal Ischemia-Reperfusion Injury

Abstract: Splenectomy and TNF-α inhibition both protect the kidney from I/R injury by reducing the accumulation of renal macrophages/monocytes and induction of major inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…It has also been demonstrated to be protective against renal ischemia-reperfusion injury. 60 In the present study, CRP (one of the indicators of an inflammatory response) was minimal under the administration of IL-6R blockade (except transiently after the operative procedures), which correlated with our previous studies. 23,53 Following xenotransplantation, we have observed a rapid decline of fT3 within hours.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It has also been demonstrated to be protective against renal ischemia-reperfusion injury. 60 In the present study, CRP (one of the indicators of an inflammatory response) was minimal under the administration of IL-6R blockade (except transiently after the operative procedures), which correlated with our previous studies. 23,53 Following xenotransplantation, we have observed a rapid decline of fT3 within hours.…”
supporting
confidence: 92%
“…We have no personal data that tumor necrosis factor alpha (TNF‐α) is important, but its perceived benefit in islet allo‐ and xenotransplantation persuaded us to incorporate a short course in our protocol. It has also been demonstrated to be protective against renal ischemia‐reperfusion injury …”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines, such as TNF‐α and IL‐6, were upregulated in I/R‐induced acute kidney injury and produce a variety of injurious changes in proximal tubular epithelial cells . Nagata et al . reported that TNF‐α inhibition can protect the kidney from I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulation of TNF-α expression is considered beneficial to protect the kidneys from injuries. Anti-TNF-α antibodies have been reported to protect the kidney from ischemia-reperfusion injury [32]. Does TNF-α modulate MC transdifferentiation in individuals with LN through ICAM-1?…”
Section: Discussionmentioning
confidence: 99%